A single-centre study on abnormal antinuclear antibodies in children caused by intravenous infusion of gamma globulin - Xu, Li; Zhou, Juan; Zhang, Yu; Wang, Yating; Yan, Xin; Wang, Li; Tang, Xuemei; Luo, Chong (Frontiers in Immunology, 2024)
To clarify the impact of intravenous infusion of gamma globulin (IVIg) on antinuclear antibodies (ANAs) in children. A retrospective analysis was performed on the data of children with nonspecific autoantibody-related diseases whose antinuclear antibody (ANA) and autoantibody profiles were detected in our hospital from January to March 2022. A total of 108 patients with a clear history of IVIg infusion within 28 days composed the IVIg group, and 1201 patients without a history of IVIg infusion composed the non-IVIg group.All patients in the IVIg group had either positive ANAs or positive autoantibodies. Anti-SSA, anti-Ro52 and anti-AMA Mi2 were the top three autoantibodies in the IVIg group. The proportions of patients who were positive for either of these three autoantibodies in the IVIg group were significantly greater than those in the non-IVIg group (all P<0.5).Spearman correlation analysis revealed that the signal intensities of anti-SSA and anti-Ro52 were negatively correlated with the number of days of ANA detection after IVIg infusion (P<0.05). Multiple logistic analyses revealed that a greater total dosage of IVIg, greater IVIg per kilogram of body weight, and fewer ANA detection days after IVIg infusion were independent risk factors for positive anti-SSA and anti-Ro52 results. It is recommended that if rheumatic diseases are suspected, ANA detection should be carried out before IVIg infusion. But for patients who are positive for at least one of these three autoantibodies after IVIg infusion, doctors should first consider adoptive antibodies.